Cervical pregnancy: A rare case report - Shakya, Beemba (Nepal Journal of Obstetrics and Gynaecology, 2020)
Cervical pregnancy accounts for less than 1% of ectopic pregnancies, with the incidence of 1 in 1,000 to 95,000 pregnancies. Here is a case report of 25 years G2P1 lady who presented with cervical pregnancy at 8 weeks and 5 days period of gestation and underwent manual vacuum aspiration under ultrasound guidance. Improved ultrasound resolution and earlier detection of these pregnancies have led to the development of more conservative treatments that attempt to limit morbidity and preserve fertility. Keywords: cervical pregnancy; manual vacuum aspiration; preserve fertility.